Hospital routines promote parent–infant closeness and cause separation in the birthing unit in the first 2 hours after birth: A pilot study. Issue 2 (15th February 2017) - Niela‐Vilén, Hannakaisa; Feeley, Nancy; Axelin, Anna
Abstract: Background: Despite the evidence of multiple benefits of early skin‐to‐skin contact, it does not always happen and infants are separated from their parents because of different hospital practices. The aim of this study was to explore parent–infant closeness and separation, and which factors promote closeness or result in separation in the birthing unit in the first 2 hours after birth from the point of view of staff members. Methods: This qualitative descriptive pilot study was conducted in one university hospital in Finland in December 2014. Midwives and auxiliary nurses working in the birthing unit were eligible for the study. The data were collected with a new application downloaded on a smartphone. The participants were asked to record all the closeness and separation events they observed between the infants and parents using the application. Results: The application was used during 20 work shifts by 14 midwives or auxiliary nurses. The participants described more closeness than separation events. Our findings indicated that the staff of the birthing unit aimed for mother–infant closeness, and father–infant closeness was a secondary goal. Closeness was mostly skin‐to‐skin contact and justified as a normal routine care practice. Infants were separated from their parents for routine measurements and because of infants' compromised health. Conclusion: Routines and normal care practices both promoted parent–infant closeness and caused separation. Parent–infant closeness and separation were controlled by staff members of the birthing unit.